The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/toxics9020041
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Marine Environment: Sources, Fates, Impacts and Microbial Degradation

Abstract: The serious global microplastic pollution has attracted public concern in recent years. Microplastics are widely distributed in various environments and their pollution is already ubiquitous in the ocean system, which contributes to exponential concern in the past decade and different research areas. Due to their tiny size coupled with the various microbial communities in aquatic habitats capable of accumulating organic pollutants, abundant literature is available for assessing the negative impact of MPs on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 186 publications
(326 reference statements)
0
39
0
Order By: Relevance
“…MPs are found in soils worldwide, especially in agricultural soils (Kumar et al 2020 ; Li et al 2020 ; Möller et al 2020 ; van den Berg et al 2020 ). They enter the soil environment in diverse ways, such as irrigation, sewage sludge, littering, and atmospheric deposition (van den Berg et al 2020 ; Yang et al 2021a , b ). MP’s vertical and horizontal mobility within the soil is regulated by various factors, including soil biota and soil characteristics.…”
Section: Effects Of Mps On the Environmentmentioning
confidence: 99%
“…MPs are found in soils worldwide, especially in agricultural soils (Kumar et al 2020 ; Li et al 2020 ; Möller et al 2020 ; van den Berg et al 2020 ). They enter the soil environment in diverse ways, such as irrigation, sewage sludge, littering, and atmospheric deposition (van den Berg et al 2020 ; Yang et al 2021a , b ). MP’s vertical and horizontal mobility within the soil is regulated by various factors, including soil biota and soil characteristics.…”
Section: Effects Of Mps On the Environmentmentioning
confidence: 99%
“…Ding et al (2019) reported that transparent MPs were preferentially selective in capturing prey by fish due to their size was closer to the diatoms. Besides, the transparent fiber with a slender shape was similar to little jellyfish or zooplankton might result in being easily mistakenly ingested by marine animals, and then enriched in their organs (Nie et al, 2019), because some low-nutrient organisms were more readily available and easily exposed to suspended microplastics (reviewed in Yang et al, 2021). Thus, the high proportion of transparent particles in coral tissue may be due to their higher heterotrophic ability and therefore such MPs were ingested by mistake.…”
Section: Microplastics Features In Coralsmentioning
confidence: 99%
“…Microplastics, a new type of pollutants, have received significant attention from scholars and the public globally. The study of microplastics pollution has become one of the current international research hotspots [ 14 , 15 , 16 , 17 , 18 ]. Recently, research reports on the sources, types, distribution, and toxicological effects of microplastics on aquatic organisms have been increasing [ 1 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%